ETLINGERA ELATIOR FLOWER OIL ANALYSIS AND ITS PROTECTION LEVEL TEST IN MOSQUITO REPELLENT LOTION - Tuslinah, Lilis (P3M STIKes Bakti Tunas Husada, 2019)
Etlingera elatior flowers contains flavonoids, terpenoids, saponins, and tannins. This study aims to determinethe content of oil compounds from Etlingera elatior flowers in n-hexan extract using the GC-MS method and tofind out their protective level towards Anopheles mosquitoes compared to the mosquito repellent lotions on themarkets. Extraction was carried out by maceration method using n-hexane solvent and it was purified using96% ethanol. The analysis oil was carried out by compound derivatization method from Etlingera elatiorflower?s oil through transesterification using sodium methanolic and analyzed using GC-MS. The analysisshowed that Etlingera elatior flower?s oil contained 22 types of compounds and five of them had % AUC valuesbetween 9 - 22.16% consisting of 9,12-octadecadienoyl chloride, 9-hexadecanoic methyl ester, octadecanoicmethyl ester, 9-octadecenoic tetradecil ester, and dodecanoic methyl ester. The results of the effectiveness test inthe form of anti-mosquito lotion showed that the mosquito repellent lotion of Etlingera elatior flower F3 (7.5%)had a significant difference with the mosquito repellent lotion that had been sold on the market